Design and Optimization of Battery Housing in Electric Cars - Bala, Abhishek; Chaitanya Kamaraju, Meher (My University, 2020)
In the current market scenario, there is fierce competition in the automotive market as the market trend shifted towards the development of e-mobility and autonomous cars. The integration of advanced technology and battery modules increases the weight and cost of the battery pack which serves the background of the project. There is a need to reduce the weight and cost of the battery pack to achieve a long-range of the vehicle. By investigating the opportunities in the battery pack, the scope was limited to battery housing components such as cross beams and bottom plates. In this thesis work, the product development approach was followed to redesign and optimize the existing battery housing of Volvo Cars in terms of weight reduction and material cost reduction with equivalent crash safety performance. Various concepts on bottom plates and cross beams were generated from idea generation activities and using methods such as topology and topography optimization. Promising concepts were selected based on the parameters such as weight, material cost, manufacturing feasibility, and crash safety parameters (intrusion and bending) in the Kesselring matrix. The final concept has been obtained as a result of refinement and the simulations driven approach and has an opportunity to fulfill the requirements. The final concept achieved 65.4% material cost reduction. There is also a possibility of merging many bottom plates in the existing concept into a few or single bottom plate with the help of the final concept. The extra weight of 6.3% and 28% intrusion loss of the final concept in comparison to the existing concept can be reduced if the final concept is redesigned. Hence, the steel material is found to be an opportunity for e-mobility to be affordable, cheaper, and sustainable in terms of environmental aspects.
Keywords: design, simulation, optimization, topology, topography, weight, cost; safety, product development, crash safety, battery pack, battery housing, battery elecric vehicles